How much is new in Brouthers et al.’s new foreign entry modes, and do they challenge the transaction cost theory of entry mode choice? - Hennart, Jean-François (Journal of International Business Studies, 2022)
Abstract Brouthers, Chen, Sali and Shaheer argue that recent increases in economic integration coupled with technological advances, such as digitization, have led to the use of new foreign market entry modes which they say have not been sufficiently acknowledged nor satisfactorily explained by an extant literature dominated by transaction cost theory (TCT). To make sense of these new entry modes, they introduce a framework based on the exploitation–exploration distinction and on embeddedness. I first outline current thinking on the TCT theory of foreign entry modes and then review Brouthers et al.’s four novel entry modes, identifying what is genuinely new about them, and what is similar to what we already know. I conclude that these four modes constitute changes in kind rather than substance, and show that they have already been satisfactorily explained using TCT. In contrast, Brouthers et al.’s exploitation–exploration–embeddedness framework is unconvincing, because (a) exploration is not an appropriate term to describe the motivation of most resource and strategic asset acquisition foreign direct investment; (b) there is considerable variation in embeddedness within some of their four novel entry modes; and (c) the availability of intermediaries breaks the hypothesized one-to-one correspondence between need for embeddedness and entry mode.